Characterization of the hybrid joint between AA2024-T3 alloy and thermoplastic composite obtained by oxy-fuel welding (OFW) - Lucas, Rafael Resende [UNESP]; de Cássia Mendonça Sales-Contini, Rita; Marques, Luis Felipe Barbosa [UNESP]; Reis, Jonas Frank [UNESP]; Abrahão, Ana Beatriz Ramos Moreira; Botelho, Edson Cocchieri [UNESP]; Mota, Rogério Pinto [UNESP] (American Institute of Mathematical Sciences (AIMS), 2024)
Studies on dissimilar materials joining have greatly increased, transitioning from temporary to permanent joining methods. The latter approach is more applicable due to the hybrid structure offering the best properties of the constituent materials, along with the development of new materials and manufacturing procedures. In this study, the AA2024-T3 alloy was treated with plasma electrolytic oxidation (PEO) and a thermoplastic composite/AA2024-T3 hybrid joint was manufactured using oxy-fuel welding (OFW). Morphological aspects, chemical compositions electrochemical and mechanical properties of hybrid composite joints were determined. The results indicated that the joint exhibits a uniform structure. The adhesion between the dissimilar materials reached a strength of 4.2 to 5.2 MPa, with cohesive bonding and without severe degradation of the thermoplastic matrix in some cases. It was observed that PEO treatment decreased the interface shear strength due to the high silicon content presence in the coating. The coatings effectively increased nobility and corrosion resistance, with corrosion rates ranging from 0.0087 to 0.018 mm/year.
Keywords: aluminum; characterization; composite; PEO; welding